Relationship between COVID-19 and use of Chlorine Dioxide Gas-Releasing Agents in Elementary Schools (Global Journal of Medical Research, 2023)
Chlorine dioxide has an inactivating effect on various types of viruses in vitro, including severe acute respiratory syndrome coronavirus 2. Therefore, chlorine dioxide gas can be used as a new preventive measure against coronavirus disease 19 (COVID-19). However, no studies have been conducted to investigate the relationship between the incidence of COVID-19 and chlorine dioxide. We retrospectively studied the occurrence of COVID-19 in 164 public elementary schools under the jurisdiction of boards of education located in urban areas in Japan, provided with chlorine dioxide gas-releasing agents or not, from January to March 2022. The odds of developing COVID-19 were lower (odds ratio: 0.934, 95% confidence interval: 0.895-0.975) in schools provided with chlorine dioxide gas-releasing agents than in schools without them. This suggested a relationship between the use of chlorine dioxide-releasing agents and the incidence of COVID-19. Further studies are needed to prove a causal relationship between them.
Keywords: chlorine dioxide; COVID-19; infection prevention; elementary school; viral infectivity